+0  
 
0
97
3
avatar

If you multiply 'a' by the sum of 'a' and 'b', you get 30. If now a + (a * b) = 30, now a * b = a + (a * b) - a². Solve for non-negative integers 'a' and 'b'.

 Jan 6, 2022
 #1
avatar
0

a = 10 and b = 2.

 Jan 6, 2022
 #3
avatar
0

a = 10 and b = 2    Oh yeah??? 

 

Problem says:  "If you multiply 'a' by the sum of 'a' and 'b', you get 30."  

 

a * (a + b) = 30 

 

10 * (10 + 2) = 30  NOT       No wonder you don't show your work. 

Guest Jan 6, 2022
 #2
avatar+675 
0

That's wrong, Guest. The solution is

 

a = 1

b = 29 .

 

But at least you tried.

 Jan 6, 2022

3 Online Users

avatar